2022
DOI: 10.1093/mspecies/seac007
|View full text |Cite
|
Sign up to set email alerts
|

Martes martes(Carnivora: Mustelidae)

Abstract: Martes martes (Linnaeus, 1758), commonly called the European pine marten, is a small predator widespread in western Eurasia. In almost all its geographic distribution, it is autochthonous. It is as a secondary consumer but, a predator with omnivorous traits. Martes martes inhabits forests with varied tree compositions, but in recent decades, it has spread to forest-steppe and agricultural areas. It is hunted in some areas, mainly in winter. In some countries during the 20th century, it experienced significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…The European pine marten Martes martes is an opportunistic mesocarnivore and forest specialist (Storch et al 1990, Brainerd and Rolstad 2002, Proulx et al 2004, Monakhov 2022) that occurs through Europe, including the British Isles, Scandinavia and the Balearic Islands, eastward to the Ural Mountains and parts of southwest Asia and the Middle East (Herrero et al 2016, Monakhov et al 2020, Monakhov 2022;2022 Supporting information, for geographical range of pine marten). The latitudinal distribution of this species aligns with the boundaries of the forest zone (Monakhov 2022). In Fennoscandia, studies have shown that pine martens prefer mature coniferous forest stands (Storch et al 1990, Brainerd and Rolstad 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The European pine marten Martes martes is an opportunistic mesocarnivore and forest specialist (Storch et al 1990, Brainerd and Rolstad 2002, Proulx et al 2004, Monakhov 2022) that occurs through Europe, including the British Isles, Scandinavia and the Balearic Islands, eastward to the Ural Mountains and parts of southwest Asia and the Middle East (Herrero et al 2016, Monakhov et al 2020, Monakhov 2022;2022 Supporting information, for geographical range of pine marten). The latitudinal distribution of this species aligns with the boundaries of the forest zone (Monakhov 2022). In Fennoscandia, studies have shown that pine martens prefer mature coniferous forest stands (Storch et al 1990, Brainerd and Rolstad 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The two species were clearly distinguishable in our analyses, and a previous study using mtDNA did not find signatures of hybridization or introgression (Inoue et al., 2010). However, a more thorough investigation is needed to understand the genomic impacts of ongoing replacement by the Japanese marten in Hokkaido, as interspecies hybridization and introgression have been reported between sable and pine marten ( M. martes ) (Modorov et al., 2020; Monakhov, 2022; Rozhnov et al., 2013), as well as between American marten ( M. americana ) and Pacific marten ( M. caurina ) in distribution boundary areas (Lucid et al., 2020).…”
Section: Discussionmentioning
confidence: 99%